Valuing health-related quality of life among the Indian population: a protocol for the Development of an EQ-5D Value set for India using an Extended design (DEVINE) Study - Atul Sharma; Manmeet Kaur; Shankar Prinja; Gaurav Jyani; Sitanshu Sekhar Kar; Mayur Trivedi; Binod Patro; Fredrick Purba; Star Pala; Swati Raman; Shalu Jain (BMJ Open)
Introduction Quality-adjusted life year (QALY) has been recommended by the government as preferred outcome measure for Health Technology Assessment (HTA) in India. As country-specific health-related quality of life tariff values are essential for accurate measurement of QALYs, the government of India has commissioned the present study. The aim of this paper is to describe the methods for the Development of an EQ-5D Value set for India using an Extended design (DEVINE) Study. Additionally, this study aspires to establish if the design of 10-time trade-off (TTO) blocks is enough to generate valid value sets.Methods and analysis A cross-sectional survey using the EuroQol Group’s Valuation Technology (EQ-VT) will be undertaken in a sample of 2700 respondents selected from six different states of India using a multistage stratified random sampling technique. The participants will be interviewed using computer-assisted personal interviewing technique. The TTO valuation will be done using 10 composite TTO (c-TTO) tasks and 7 discrete choice experiment (DCE) tasks. Hybrid modelling approach using both c-TTO and DCE data to estimate the potential value set will be applied. Values of all 3125 health states will be predicted using both the conventional EQ-VT design of 10 blocks of 10 TTO tasks, and an extended design of 18 blocks of 10 TTO tasks. The potential added value of the eight additional blocks in overall validity will be tested. The study will deliver value set for India and assess the adequacy of existing 10-blocks design to be able to correctly predict the values of all 3125 health states.Ethics and dissemination The ethical approval has been obtained from Institutional Ethics Committee of PGIMER, Chandigarh, India. The anonymised EQ-5D-5L value set will be available for general use and in the HTAs commissioned by India’s central HTA Agency.